In vitro Antioxidant and Lipid Peroxidation inhibitory properties of Baccaurea angulata fruit extracts - Ahmed, Idris Adewale; Mikail, Maryam Abimbola; Ibrahim, Muhammad; Hazali, Norazlanshah; Abdull Rasad, Mohammad Syaiful Bahari; Arief Ichwan, Solachuddin Jauhari; Abdul Ghani, Radiah; Yahya, Mohammad Noor Adros (2013)
Lipids and lipid-containing foods are prone to peroxidation during processing and storage. Thus, antioxidants are required to extend food shelf life and prevent food deterioration. The consumption of dietary antioxidants is also beneficial in preventing cardiovascular diseases, particularly atherosclerosis. The aim of this study was to evaluate the antioxidant property of a local underutilised fruit, Baccaurea angulata. The whole fruit, skin and berry were extracted using two solvents which were phosphate buffered saline (PBS) and methanol. The various extracts were explored for the prevention or delaying of lipids oxidation using thiobarbituric acid (TBA) method based on inhibition of linoleic acid peroxidation and lipid peroxidation assays. Freeze-dried whole fruit (FDWF), freeze-dried berry (FDB) and freeze-dried skin (FDS) extracts were also analysed for total phenolic, total flavonoid, total anthocyanin and total carotene. The results showed that, lyophilized skin (FDS) contained the highest flavonoid compound of 31.05 mg QE/g and anthocyanin compound, as compared to other samples. The yield of the crude extracts obtained from FDB was the highest. The overall result also showed that methanolic extracts remarkably inhibited lipid peroxidation in the two assays, while PBS extracts showed only average inhibition. It was also observed that the methanolic extracts of FDB (87.9%) and FDWF (80.9%) showed the highest inhibition in lipid peroxidation and linoleic acid peroxidation assays respectively. Hence, the various parts of B. angulata could be recommended to be incorporated in daily meal preparations and for other neutraceuticals.